2016
DOI: 10.1371/journal.pone.0155946
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of AKT Signalling by Ursolic Acid Induces Intrinsic Apoptosis and Sensitization to Doxorubicin in Soft Tissue Sarcoma

Abstract: Several important biological activities have been attributed to the pentacyclic triterpene ursolic acid (UA), being its antitumoral effect extensively studied in human adenocarcinomas. In this work, we focused on the efficacy and molecular mechanisms involved in the antitumoral effects of UA, as single agent or combined with doxorubicin (DXR), in human soft tissue sarcoma cells. UA (5–50 μM) strongly inhibited (up to 80%) the viability of STS cells at 24 h and its proliferation in soft agar, with higher concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In this regard, UA seems to be an interesting target to develop new formulations to be used in human health, because different reports demonstrated its multivalent activities against pathological conditions. UA was demonstrated to be active against different tumor cell lines (Chuang et al., 2016, Aguiriano-Moser et al., 2015, Kim and Moon, 2015), its anti-tumoral effect being associated to apoptosis induction by intrinsic and extrinsic pathways of death (Li et al., 2014, Meng et al., 2015, Zhang et al., 2016, Villar et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, UA seems to be an interesting target to develop new formulations to be used in human health, because different reports demonstrated its multivalent activities against pathological conditions. UA was demonstrated to be active against different tumor cell lines (Chuang et al., 2016, Aguiriano-Moser et al., 2015, Kim and Moon, 2015), its anti-tumoral effect being associated to apoptosis induction by intrinsic and extrinsic pathways of death (Li et al., 2014, Meng et al., 2015, Zhang et al., 2016, Villar et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified that the growth-inhibitory function of p21 is closely related to its intracellular localization [ 13 , 31 ], whereas cytoplasmic re-localization resulting from phosphorylation of p21 was associated with anti-apoptotic behaviors [ 32 ]. P-AKT was able to phosphorylate p21 at T145, and transfer p21 to the cytoplasm, where it promotes cell growth and suppresses cell apoptosis [ 12 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo anticancer activity of betulinic acid was identified using xenograft models [ 10 , 11 ]. The ursolic acid can also induce apoptosis, autophagy, and cell cycle arrest through various pathways, such as inhibition of DNA replication, stimulation of reactive oxygen species (ROS) production, and affecting the balance between proapoptotic and antiapoptotic proteins [ 6 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%